Synthesis of Pyrrolo[2,3-d]pyrimidin-4-ones(7-deazapurines) Under Solvent- and Catalyst-Free Conditions - DAVOODNIA, A.; BAKAVOLI, M.; KHASHI, M.; MOLOUDI, R.; TAVAKOLI-HOSEINI, N. (Asian Journal of Chemistry, 2010)
A facile one-pot synthesis of some new 3,7-dihydro-4H-pyrrolo[2,3- d]pyrimidin-4-ones in good yields has been developed through cyclocondensation of 2-amino-1H-pyrrole-3-carboxamides with triethyl orthoesters in solvent- and catalyst-free conditions.